VS4‐Decorated Carbon Nanotubes for Lithium Storage with Pseudocapacitance Contribution. Issue 6 (26th July 2019) - Wang, Sen; Ma, Wenjun; Zang, Xinyue; Ma, Linzheng; Tang, Lin; Guo, Jinxue; Liu, Qingyun; Zhang, Xiao
Abstract: The application of metal oxides and sulfides for lithium‐ion batteries (LIBs) is hindered by the limited Li + diffusion kinetics and inevitable structural damage. Pseudocapacitance for electrochemical lithium storage provides an effective and competitive solution for developing electrode materials with large capacity, high rate capability, and stability. Herein, a composite composed of VS4 nanoplates tightly bound to carbon nanotubes (VS4 /CNTs) is developed to demonstrate pseudocapacitance‐assisted lithium storage. The texture of the assembled VS4 nanoplates supplies efficient electrolyte/ion diffusion, as well as exposed surface for pseudocapacitive behavior. The effective coupling between VS4 and CNTs ensures fast electron transfer and high stability. The VS4 /CNTs anode exhibits high capacity of 1144 mAh g −1 at 0.1 A g −1, superior cycling stability (capacity retention of 100 % at 1 A g −1 after 400 cycles), and good rate capability. The pseudocapacitive behavior plays an important role in determining the excellent electrochemical properties, contributing to the increased charge rate and reaching as high as 42 % of the total charge at a scan rate of 1 mV s −1 . This study demonstrates the potential application of metal sulfides with pseudocapacitive contribution in LIBs. Abstract : Superior storage : VS4 nanoplates tightly bound to carbon nanotubes (CNTs) demonstrate pseudocapacitance‐assisted lithium storage. The effective coupling between VS4 and CNTs ensures fast electron transfer and high stability. The VS4 /CNTs anode exhibits high capacity, superior cycling stability, and good rate capability and indicates the potential application of metal sulfides with pseudocapacitive contribution in lithium‐ion batteries.